2017
DOI: 10.1371/journal.pone.0178049
|View full text |Cite
|
Sign up to set email alerts
|

In vivo transduction of neurons with TAT-UCH-L1 protects brain against controlled cortical impact injury

Abstract: Many mechanisms or pathways are involved in secondary post-traumatic brain injury, such as the ubiquitin-proteasome pathway (UPP), axonal degeneration and neuronal cell apoptosis. UCH-L1 is a protein that is expressed in high levels in neurons and may have important roles in the UPP, autophagy and axonal integrity. The current study aims to evaluate the role of UCH-L1 in post-traumatic brain injury (TBI) and its potential therapeutic effects. A novel protein was constructed that fused the protein transduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Mild TBI involves complex pathophysiologic processes associated with microscopic shearing of cells in the central nervous system secondary to traumatic biomechanical forces to the head (8). Such shearing induces damage to the cell, resulting in the release of neuronal and astrocytic proteins or cell-free DNA (cfDNA) not normally found in the extracellular space (9), including glial fibrillary acidic protein (GFAP) (10), ubiquitin carboxyl-terminal hydrolase L1 (UCH-L1) (11), and Tau (12). Tau is a microtubule stabilizing protein abundant in neurons (13), and released into the extracellular space upon neuronal damage (14).…”
Section: Introductionmentioning
confidence: 99%
“…Mild TBI involves complex pathophysiologic processes associated with microscopic shearing of cells in the central nervous system secondary to traumatic biomechanical forces to the head (8). Such shearing induces damage to the cell, resulting in the release of neuronal and astrocytic proteins or cell-free DNA (cfDNA) not normally found in the extracellular space (9), including glial fibrillary acidic protein (GFAP) (10), ubiquitin carboxyl-terminal hydrolase L1 (UCH-L1) (11), and Tau (12). Tau is a microtubule stabilizing protein abundant in neurons (13), and released into the extracellular space upon neuronal damage (14).…”
Section: Introductionmentioning
confidence: 99%
“…UCHL1 protein fused to the protein transduction domain of HIV-transactivating transduction protein (TAT-UCHL1) can transduce neurons after intraperitoneal (i.p.) injection into mice [ 101 ]. In a controlled cortical impact (CCI) injury model of post-traumatic brain injury, TAT-UCHL1 treatment improved function of the ubiquitin-proteasome pathway, decreased activation of autophagy after CCI, attenuated axonal injury and increased hippocampal neuronal survival after CCI [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in rat models have shown that the concentration of UCH-L1 increases in the presence of brain damage (14), and the elevation in UCH-L1 levels reaches a peak at 6 hours after birth in brain-damaged human neonates (15). During HIE, brain injury results in the release of inflammatory factors, excessive production of free radicals, and other related phenomena, which interact with each other, leading to degeneration, necrosis, and apoptosis of brain neurons and the destruction of the blood-brain barrier (16)(17)(18). At this time, the brain releases a large amount of UCH-L1 protein which enters the blood through the damaged blood-brain barrier, and can thus be detected in the cerebrospinal fluid or blood during the acute stage of brain injury (19,20).…”
Section: Discussionmentioning
confidence: 99%